The Influence of Work Motivation and Work Discipline on the Performance of Employees (Marketing Division) Insurance XYZ Jabodetabek Area - Sarla Martiza Maula Putri; Muhammad Takrim (Research Trend in Technology and Management, 2025)
This study examines how Work motivation and discipline are both important factors in achieving success influence The performance of employees is important Marketing Division of XYZ Insurance in the Jabodetabek area, focusing particularly on Branch B, which has failed to meet its performance targets. The study aims to identify the reasons for this and propose solutions. Quantitative methods and purposive sampling techniques were employed to data Questionnaires were used to collect the data to 98 respondents. Linear regression, t-tests, F-tests and the coefficient of determination are used to analyse data are all used were then used to analyse the data. Find out what the results are showed that work Employee performance is positively and significantly impacted by motivation and discipline, which in turn can lead to improved productivity and enhanced organisational outcomes (t count = 2.739, sig. = 0.007 and t count = 5.495, sig. <0.001, respectively). Additionally, the combined effect Motivation and work discipline are both important factors influence performance was Positive and significant, with a strong impact (F-count = 40.890; sig. <0.001). The obtained regression equation (Y = 9.132 + 0.206X₁ + 0.419X₂) indicates that work discipline exerts a stronger influence. The coefficient of determination (R²) of 0.457 indicates that these two variables can explain 45.7% of the variation in performance. Therefore, this study concludes The Work motivation and discipline have a positive impact on employee performance and significant marketing division. Consequently, companies are advised to enhance employee motivation and discipline to encourage continuous performance improvement.